Treatment with denosumab reduces secondary fracture risk in women with postmenopausal osteoporosis. (2nd November 2015) - Palacios, S.; Kalouche-Khalil, L.; Rizzoli, R.; Zapalowski, C.; Resch, H.; Adachi, J. D.; Gallagher, J. C.; Feldman, R. G.; Kendler, D. L.; Wang, A.; Wagman, R. B.; Adami, S.
Abstract : Objectives A history of prior fracture is one of the strongest predictors of a future fragility fracture. In FREEDOM, denosumab significantly reduced the risk of new vertebral, non-vertebral, and hip fractures. We carried out a post-hoc analysis of FREEDOM to characterize the efficacy of denosumab in preventing secondary fragility fractures in subjects with a prior fracture. Methods A total of 7808 women aged 60–90 years with a bone mineral density T -score of less than − 2.5 but not less than − 4.0 at either the lumbar spine or total hip were randomized to subcutaneous denosumab 60 mg or placebo every 6 months for 36 months. The anti-fracture efficacy of denosumab was analyzed by prior fracture status, to assess secondary fragility fracture, and by subject age, prior fracture site and history of prior osteoporosis medication use. Results A prior fragility fracture was reported for 45% of the overall study population. Compared with placebo, denosumab significantly reduced the risk of a secondary fragility fracture by 39% (incidence, 17.3% vs. 10.5%; p < 0.0001). Similar results were observed regardless of age or prior fracture site. In the overall population, denosumab significantly reduced the risk of a fragility fracture by 40% (13.3% vs. 8.0%; p < 0.0001), with similar results observed regardless of history of prior osteoporotic medication use. Conclusions Denosumab reduced the risk of fragility fractures to a similar degree in all risk subgroups examined, including those with prior fragility fractures. Identifying and treating high-risk individuals could help to close the current care gap in secondary fracture prevention.